Partial Hearing Preservation after Translabyrinthine Vestibular Schwannoma Resection: Case Report and Review of the Literature - Syed F. Ahsan; Dennis Bojrab Jr.; Robert Standring (Journal of Neurological Surgery Reports, 2015)
Abstract